The Approach of Consumer Reviews to Product Competitiveness and Management Strategies - Negara, Dharma Setiawan; Darmawan, Didit; Gardi, Bayar (Journal of Social Science Studies, 2021)
Consumer reviews and recommendations have become a significant factor in shaping a company's competitive position in the digital age. Consumers are increasingly relying on online reviews and recommendations before making purchasing decisions so companies must be able to strategically manage such feedback. This research aims to analyze how customer reviews affect business competitiveness and the strategies that can be implemented to optimize the benefits of these reviews. The research method used is a literature study by reviewing various academic sources and case studies from various industries. The results show that positive reviews can increase consumer trust and attract new customers, while negative reviews can adversely affect a company's reputation if not handled properly. Companies that are able to respond to reviews professionally and build good interactions with customers tend to have a stronger image in the market. The use of technologies such as big data and Artificial Intelligence (AI) to analyze customer reviews can help companies understand market trends and improve service quality. The conclusion of this study confirms that customer reviews are not only a form of feedback, but also a strategic tool to build a competitive advantage. Companies need to develop effective strategies to proactively manage reviews to improve competitiveness and consumer loyalty.